The Effect of Watermelon Juice Supplementation on Perceived Recovery and Anaerobic Power Recovery in Young Karate Athletes - Gifran Rihla Gifarka Latief; Samsul Bahri; Rini Syafiarini; Muhamad Fahmi Hasan (Universitas Pendidikan Indonesia, 2022)
Karate is a popular and often played martial sport. Due to the limited recovery period experienced by karate athletes during matches, they must employ an appropriate recovery plan in order to regain their initial condition. Watermelon research has become popular in recent years for application in sports. This clinical trial used one crossover design. The participants in this study were young karate athletes supported by the West Java student education and training center. The subject will undergo two periods: the first during which he or she will not consume any watermelon juice, and the second during which he or she will consume 500ml of watermelon juice daily for seven days. The data collection procedure includes measuring perceived recovery status to evaluate the degree of perceived recovery, and also anaerobic ability through a running-anaerobic sprint test. After the sample had completed the protocol in the form of a match simulation, measurements were taken. The results indicated that drinking watermelon juice had a significant effect on perceived recovery status 48 hours after and 72 hours after the treatment. However, after consuming watermelon juice, there was no significant difference in the athlete's anaerobic abilities. Consumption of watermelon juice can aid athletes in their recovery process, which has an effect on the athlete's reported recovery state. It does not, however, contribute to the recovery of anaerobic capability.